Size-regulated group separation of CoFe2O4 nanoparticles using centrifuge and their magnetic resonance contrast properties - Kang, Jongeun; Lee, Hyunseung; Kim, Young-Nam; Yeom, Areum; Jeong, Heejeong; Lim, Yong Taik; Hong, Kwan Soo (Nanoscale research letters, 2013)
Magnetic nanoparticle (MNP)-based magnetic resonance imaging (MRI) contrast agents (CAs) have been the subject of extensive research over recent decades. The particle size of MNPs varies widely and is known to influence their physicochemical and pharmacokinetic properties. There are two commonly used methods for synthesizing MNPs, organometallic and aqueous solution coprecipitation. The former has the advantage of being able to control the particle size more effectively; however, the resulting particles require a hydrophilic coating in order to be rendered water soluble. The MNPs produced using the latter method are intrinsically water soluble, but they have a relatively wide particle size distribution. Size-controlled water-soluble MNPs have great potential as MRI CAs and in cell sorting and labeling applications. In the present study, we synthesized CoFe 2 O 4 MNPs using an aqueous solution coprecipitation method. The MNPs were subsequently separated into four groups depending on size, by the use of centrifugation at different speeds. The crystal shapes and size distributions of the particles in the four groups were measured and confirmed by transmission electron microscopy and dynamic light scattering. Using X-ray diffraction analysis, the MNPs were found to have an inverse spinel structure. Four MNP groups with well-selected semi-Gaussian-like diameter distributions were obtained, with measured T 2 relaxivities ( r 2 ) at 4.7 T and room temperature in the range of 60 to 300 mM −1 s −1 , depending on the particle size. This size regulation method has great promise for applications that require homogeneous-sized MNPs made by an aqueous solution coprecipitation method. Any group of the CoFe 2 O 4 MNPs could be used as initial base cores of MRI T 2 CAs, with almost unique T 2 relaxivity owing to size regulation. The methodology reported here opens up many possibilities for biosensing applications and disease diagnosis. PACS 75.75.Fk, 78.67.Bf, 61.46.Df